The Importance of Money in Shaping Employee Intention to Stay In Small Businesses: The Moderating Roles of Growth Mindset and Caring Climate - Martinus Parnawa Putranta; Russel P.J. Kingshott; Debora Wintriarsi Handoko; Theresia Agung Maryudi Harsiwi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
Employee retention is a critical challenge for small and medium enterprises (SMEs), particularly in developing economies like Indonesia, where financial constraints and high turnover rates jeopardize organizational stability. This study investigates the relationship between monetary importance and intention to stay, moderated by caring climate and growth mindset. Using purposive sampling, data were collected through an online survey from 198 employees of small businesses in Central Java, all of whom had worked for their organizations for at least one year. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results revealed that monetary importance did not have a significant direct effect on intention to stay. However, caring climate positively moderated this relationship, enhancing retention through a supportive and empathetic workplace environment. In contrast, growth mindset negatively moderated the relationship, suggesting that employees with a strong growth orientation prioritize non-financial motivators such as professional development opportunities. These findings highlight the importance of tailoring retention strategies to individual and contextual factors, combining financial incentives with non-monetary approaches. This study contributes to the literature on retention strategies by integrating organizational and psychological perspectives within the SME context.